2010
DOI: 10.1159/000289864
|View full text |Cite
|
Sign up to set email alerts
|

C-Peptide as a Therapeutic Tool in Diabetic Nephropathy

Abstract: Background/Aims: Insulin is synthesised as a pro-hormone with an interconnecting C-peptide, cleaved during post-translational modification. This review discusses growing evidence which indicates that C-peptide is biologically active, benefiting microvascular complications associated with diabetes. Methods: To explore the renoprotective role of C-peptide in diabetic nephropathy (DN), we reviewed the literature using PubMed for English language articles that contained key words related to C-peptide, kidney and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 103 publications
2
46
0
1
Order By: Relevance
“…(Fiorina et al 2003(Fiorina et al , 2005. Recent studies have indicated that C-peptide produced by islet cells might help to prevent and treat diabetic microvascular lesions (Cotter et al 2003, Forst & Kunt 2004, Hills et al 2010. In fact, several human trials and animal studies have demonstrated that C-peptide can improve the kidney structural and functional abnormalities of diabetic nephropathy (Hills et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Fiorina et al 2003(Fiorina et al , 2005. Recent studies have indicated that C-peptide produced by islet cells might help to prevent and treat diabetic microvascular lesions (Cotter et al 2003, Forst & Kunt 2004, Hills et al 2010. In fact, several human trials and animal studies have demonstrated that C-peptide can improve the kidney structural and functional abnormalities of diabetic nephropathy (Hills et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that C-peptide produced by islet cells might help to prevent and treat diabetic microvascular lesions (Cotter et al 2003, Forst & Kunt 2004, Hills et al 2010. In fact, several human trials and animal studies have demonstrated that C-peptide can improve the kidney structural and functional abnormalities of diabetic nephropathy (Hills et al 2010). Samnegard et al (2005) reported a marked decrease in proteinuria and mesangial matrix synthesis in diabetic nephropathy rats treated with Cpeptide compared with those treated with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…A cleavage product of pro-insulin, C-peptide exerts a number of protective affects against the micro-vascular and macro-vascular complications associated with hyperglycaemia in type I diabetes [127] and in those patients with DN, C-peptide is reno-protective [128]. Recently, the Connecting-peptide has been…”
Section: Therapeutic Interventionmentioning
confidence: 99%
“…Although C-peptide has reversal effects on the fibrosis of glomerular in DN (18)(19)(20)(21)(22), the underlying mechanism is not clarified. Insufficient MMP-2 and MMP-9 is considered to be a contributor of ECM accumulation (11).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of C-peptide along with insulin is the primary feature of type 1 DM and late stage of type 2 DM (16). C-peptide has been found to have unique beneficial effects on DN, attenuating glomerular and tubular injury (17)(18)(19). Physiological concentration of C-peptide can reverse the fibrosis of glomerular and recover renal function in .…”
mentioning
confidence: 99%